STRATEGI PENGEMBANGAN KAWASAN PELABUHAN PERIKANAN NUSANTARA UNTIA BERBASIS EKOWISATA DI KOTA MAKASSAR - Muhammad Ardiansyah; Danial Danial; Muhammad Jamal Alwi (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2020)
Strategy For Development of Untia Archipelago Fishing Area Based on Ecotourism In The City of Makassar This research was conducted from August 5, 2019 to September 5, 2019, aimed at identifying the potential of ecotourism in the Untia VAT Area mangrove ecosystem, analyzing the suitability of the Untia VAT Area mangrove ecotourism, and determining the strategy of developing mangrove ecotourism in the Untia VAT Area. Data collection was carried out through field surveys and interviews using questionnaires. Data analysis uses area suitability analysis for coastal tourism, mangrove tourism category and SWOT analysis. The results of this study indicate that the potential for ecotourism in the mangrove ecosystem Untia VAT Area is a mangrove area included in the appropriate category to be used as an ecotourism area. The strategy of developing mangrove ecotourism in the Untia PPN Region is to increase human resources (HR), planting abrasion-resistant mangrove species in a sustainable manner, procurement of facilities and infrastructure to support tourism activities, and good cooperation among policy makers.